Impact of Maternal Consumption of Cannabis, Opioids, and Alcohol on Neurodevelopment in the Short and Long Term: A Comparison - Canizales, Andrea (2023)
The use of psychoactive substances during pregnancy has exhibited a growing trend in recent years and is now recognized as a significant public health problem due to its high morbidity and maternal-fetal mortality rates. Among the psychoactive substances, alcohol and cannabis are the most frequently consumed during pregnancy, while opioids have shown a significant increase in usage by pregnant mothers due to their analgesic effects. The chemical properties of these substances, such as their high permeability at the placental barrier and their passage into breast milk, are factors that influence their ability to directly impact the fetus or infant, posing a potential danger to neurodevelopment. These substances can disrupt the normal development of the central nervous system (CNS) during embryogenesis and the neonatal period. Maternal consumption of these substances during critical periods of embryonic development can lead to short-term effects such as neuronal migration errors, structural brain development, craniofacial anatomical alterations, and long-term consequences like psychomotor development issues, language impairment, and cognitive dysfunctions. This article aims to compare the impact of maternal consumption of cannabis, opioids, and alcohol on neurodevelopment in the short and long term. The research was conducted using bibliographic engines including Pubmed, Embase, Scielo, and UptoDate with the following keywords: "cannabis," "marijuana," "alcohol," "ethanol," "opioids," "pregnancy," "maternal," "neurodevelopment," and "brain development." The inclusion criteria encompassed original research articles, systematic literature reviews, guidelines, topic reviews, and case reports in both English and Spanish.